2013
DOI: 10.1161/atvbaha.112.301052
|View full text |Cite
|
Sign up to set email alerts
|

CD34 Hybrid Cells Promote Endothelial Colony-Forming Cell Bioactivity and Therapeutic Potential for Ischemic Diseases

Abstract: Objective-Although endothelial progenitor cells (EPCs) have been reported to promote neovessel formation during vascular injury, the function of supporting cells of EPCs and their interaction with EPCs during EPC isolation remain unclear. Approach and Results-We investigated the functional properties of 2 types of EPCs, also known as endothelial colonyforming cells (ECFCs), CD34− /CD34 + cell-derived ECFCs (hybrid-dECFCs) and CD34 + cell-derived ECFCs (stemdECFCs), isolated using different methods, to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…20 In recent years, several groups have reported the effects of various genes and proteins on the function, differentiation, and migration of circulating progenitor cells both in vivo and in vitro. 21,22 For instance, bone marrow protein 9, a member of the transforming growth factor-β family, has been indicated to contribute to the differentiation of the endothelial progenitor cells. 23 The expression of bone marrow protein 9 and its receptor, activin receptor-like kinase 1, was greatly altered during the differentiation of these progenitor cells.…”
Section: Circulating Progenitor Cells and Inflammationmentioning
confidence: 99%
“…20 In recent years, several groups have reported the effects of various genes and proteins on the function, differentiation, and migration of circulating progenitor cells both in vivo and in vitro. 21,22 For instance, bone marrow protein 9, a member of the transforming growth factor-β family, has been indicated to contribute to the differentiation of the endothelial progenitor cells. 23 The expression of bone marrow protein 9 and its receptor, activin receptor-like kinase 1, was greatly altered during the differentiation of these progenitor cells.…”
Section: Circulating Progenitor Cells and Inflammationmentioning
confidence: 99%
“…EPCs were isolated from human umbilical cord blood 26,27 obtained from donors at Pusan National University Hospital (PNUH, Yangsan, South Korea). All procedures were as described in a protocol approved by the Institutional Review Board of PNUH (Approval No.…”
Section: Cell Culture Cell Isolation and Culturementioning
confidence: 99%
“…The cells were still healthy and continued to proliferate at passage 6 and above. 26,27 spheroid culture of ePcs…”
Section: Cell Culture Cell Isolation and Culturementioning
confidence: 99%
“…30 Accordingly, early application of this cell population was made in patients with critical limb ischemia and was shown to impart benefit on the risk of amputation. 31,32 Furthermore, in patients with angina refractory to medical therapy, the CD34 + population has been implanted, providing initial evidence for diminished frequency of angina noted. 33-35 This was more formally evaluated in the ACT34-CMI trial that demonstrated evidence for improvement in exercise performance.…”
Section: Introductionmentioning
confidence: 99%